Corporate governance and the global financial crisis international perspectives - Sun, William, 1962-; Stewart, Jim, 1952-; Pollard, David, 1946-; ProQuest (Firm) (Cambridge ; New York : Cambridge University Press, 2011)
"Over the last two decades there has been a notable increase in the number of corporate governance codes and principles, as well as a range of improvements in structures and mechanisms. Despite this, corporate governance failed to prevent a widespread default of fiduciary duties of corporate boards and managerial responsibilities in the finance industry, which contributed to the 2007-2010 global financial crisis. This book brings together leading scholars from North America, Europe, Asia-Pacific and the Middle East to provide fresh and critical analytical insights on the systemic failures of corporate governance linked to the global financial crisis. Contributors draw from a range of disciplines to demonstrate the severe limitations of the dominant corporate governance framework and its associated market-oriented approach. They provide suggestions on how the governance problems could be tackled to prevent or mitigate any future financial crisis and explore new directions for post-crisis corporate governance research and reforms"--
Rethinking corporate governance : lessons from the global financial crisis / William Sun, Jim Stewart and David Pollard -- The failure of corporate governance and the limits of law : British banks and the global financial crisis / Roman Tomasic -- Where was the 'market for corporate control' when we needed it? / Blanaid Clarke -- Information asymmetry and information failure : disclosure problems in complex financial markets / Steven L. Schwarcz -- Finance, governance and management : lessons to be learned from the current crisis / Roland Perez -- A review of corporate governance in UK banks and other financial industry entities : the role of institutional shareholders / Robert A. G. Monks -- Ownership structure and shareholder engagement : reflections on the role of institutional shareholders in the financial crisis / Roger Barker -- Board challenges 2009 / Jay W. Lorsch -- Do independent boards effectively monitor management? : evidence from Japan during the financial crisis / Chunyan Liu, Jianlei Liu and Konari Uchida -- Risk management in corporate law and corporate governance / Christoph Van der Elst -- Corporate governance, capital market regulation and the challenge of disembedded markets / Peer Zumbansen -- The focus of regulatory reforms in Europe after the global financial crisis : from corporate to contract governance / Florian Möslein -- The great recession's impact on global corporate governance / James Shinn -- Corporate governance in the Islamic finance industry and mitigation of risks in the post global financial crises / Nasser Saidi -- A holistic approach to corporate governance : lessons from the financial crisis and the way forward / Suzanne Young and Vijaya Thyil.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Corporate governance; Global Financial Crisis, 2008-2009.; Electronic books